Influence of Corynebacterium pseudotuberculosis infection on level of acute phase proteins in goats - Jeber, Z. K. H.; Md. Jinin @ Md. Janin, Zurin Azlin @ Zurinazlin; Abdullah, Faez Firdaus Jesse; Saharee, Abdul Aziz; Sabri, Jasni; Yusoff, Rosnina; Haron, Abd Wahid (BioMed Central, 2016)
Background: Goat caseous lymphadenitis (CLA) is a chronic disease caused by Corynebacterium pseudotuberculosis. However, there is paucity of data about goat's acute phase response during the course of CLA. This study was conducted to investigate the response of acute phase proteins, mainly haptoglobin (Hp), serum amyloid A (SAA) and the negative acute phase response, especially albumin after an experimental challenge of C. pseudotuberculosis and phospholipase D (PLD) in Cross bred Boer goats. Results: Serum Hp concentration in goats challenged with C. pseudotuberculosis (inoculated with 1x109 cfu subcutaneously) showed a significant increase, 5 fold in males (0.98±0.12mg/ml) and 3 fold in females (0.66±0.12mg/ml) compared to the control (0.2±0.02mg/ml). Challenge with PLD (1ml/20kg body weight intravenously) also showed significant increase, 4 fold in males and females (0.89±0.11mg/ml; 0.82±0.12mg/ml) respectively compared to the control (0.2±0.02mg/ml). Albumin concentration showed a significant decrease in both treated groups compared to the control. There were no significant changes in SAA concentration between challenged and control goats. Conclusions: There was a significant response by Hp to C. pseudotuberculosis infection and PLD challenge. This was supported by the early acute response in which Hp was detected before CLA lesions were developed. Therefore, it concluded that C. pseudotuberculosis and PLD can influence the level of acute phase proteins in goats.